Primary Care Providers' Knowledge and Practices of Diabetes Management During Ramadan - Mujtaba Ali; Alexandra Adams; Md Anwar Hossain; David Sutin; Benjamin Hyun Han (SAGE Publishing, 2016)
There are an estimated 3.5 million Muslims in North America. During the holy month of Ramadan, healthy adult Muslims are to fast from predawn to after sunset. While there are exemptions for older and sick adults, many adults with diabetes fast during Ramadan. However, there are risks associated with fasting and specific management considerations for patients with diabetes. We evaluated provider practices and knowledge regarding the management of patients with diabetes who fast during Ramadan. A 15-question quality improvement survey based on a literature review and the American Diabetes Association guidelines was developed and offered to providers at the outpatient primary care and geriatric clinics at an inner-city hospital in New York City. Forty-five providers completed the survey. Most respondents did not ask their Muslim patients with diabetes if they were fasting during the previous Ramadan. Knowledge of fasting practices during Ramadan was variable, and most felt uncomfortable managing patients with diabetes during Ramadan. There is room for improvement in educating providers about specific cultural and medical issues regarding fasting for patients with diabetes during Ramadan.